Metabolomics-based response of Salmonella to desiccation stress and skimmed milk powder storage - Li, Shaoting; Chen, Yingqi; Zeng, Ji; Zeng, Haiyan; Ma, Zhuolin; Chen, Siyi; Yang, Yuheng; Zhang, Hongmei (Frontiers in Microbiology, 2023)
The strong survival ability of Salmonella in low-moisture foods (LMFs) has been of public concern, and is considered a threat to people's health. Recently, the development of omics technology has promoted research on the molecular mechanisms of the desiccation stress response of pathogenic bacteria. However, multiple analytical aspects related to their physiological characteristics remain unclear. We explored the physiological metabolism changes of S. enterica Enteritidis exposed to a 24h-desiccation treatment and a subsequent 3-month desiccation storage in skimmed milk powder (SMP) with an approach of gas chromatography-mass spectrometry (GC-MS) and ultra performance liquid chromatography-Q Exactive-mass spectrometry (UPLC-QE-MS). A total of 8292 peaks were extracted, of which 381 were detected by GC-MS and 7911 peaks were identified by LC-MS/MS, respectively. Through analyses of differentially expressed metabolites (DEMs) and key pathways, a total of 58 DEMs emerged from the 24h-desiccation treatment, which exhibited the highest relevance for five metabolic pathways, involving glycine, serine, and threonine metabolism, pyrimidine metabolism, purine metabolism, vitamin B6 metabolism, and pentose phosphate pathway. After 3-month SMP storage, 120 DEMs were identified, which were related to several regulatory pathways including arginine and proline metabolism, serine and threonine metabolism, β-alanine metabolism, glycerolipid metabolism, and glycolysis. The analyses of key enzyme activities of XOD, PK, and G6PDH and ATP content provided further evidence that supported the metabolic responses such as nucleic acid degradation, glycolysis, and ATP production played an important role in Salmonella’s adaptation to desiccation stress. This study enables a better understanding of metabolomics-based responses of Salmonella at the initial stage of desiccation stress and the following long-term adaptive stage. Meanwhile, the identified discriminative metabolic pathways may serve as potentially useful targets in developing strategies for the control and prevention of desiccation-adapted Salmonella in LMFs..